Identification of uropathogens and antimicrobial resistance of urinary tract infections at tertiary medical college in Bangladesh - Orchee, Noshin Tabassum (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2024.